Segmentation vessel in Fundus with Isotropic Undecimated Wavelet Transform (IUWT) and Fuzzy Hysteresis Thresholding (FHT) - Putri Nur Rahayu; Asti Riani Putri (Department of Electrical Engineering ITS and FORTEI, 2019)
Segmentation of blood vessels in fundus can used to detect diabetic retinopathy disease by looking at the characteristic of blood vessel characteristic of thin and thick blood vessels. In this research, the combination of isotropic undecimated wavelet transform (IUWT) and Fuzzy hysteresis thresholding (FHT) are used for blood vessel segmentation to segmented for thin and thick vessels . In this research Accuracy value 0.95, precision 0.88, TPR 0.62, FPR 0.008.Keywords: fuzzy, hysteresis thresholding, isotropic undecimated wavelet transform, segmentation vessel.